A new three dimensional biomimetic hydrogel to deliver factors secreted by human mesenchymal stem cells in spinal cord injury. (January 2016) - Caron, Ilaria; Rossi, Filippo; Papa, Simonetta; Aloe, Rossella; Sculco, Marika; Mauri, Emanuele; Sacchetti, Alessandro; Erba, Eugenio; Panini, Nicolò; Parazzi, Valentina; Barilani, Mario; Forloni, Gianluigi; et al.
Abstract: Stem cell therapy with human mesenchymal stem cells (hMSCs) represents a promising strategy in spinal cord injury (SCI). However, both systemic and parenchymal hMSCs administrations show significant drawbacks as a limited number and viability of stem cells in situ. Biomaterials able to encapsulate and sustain hMSCs represent a viable approach to overcome these limitations potentially improving the stem cell therapy. In this study, we evaluate a new agarose/carbomer based hydrogel which combines different strategies to optimize hMSCs viability, density and delivery of paracrine factors. Specifically, we evaluate a new loading procedure on a lyophilized scaffold (soaked up effect) that reduces mechanical stress in encapsulating hMSCs into the hydrogel. In addition, we combine arginine–glycine–aspartic acid (RGD) tripeptide and 3D extracellular matrix deposition to increase the capacity to attach and maintain healthy hMSCs within the hydrogel over time. Furthermore, the fluidic diffusion from the hydrogel toward the injury site is improved by using a cling film that oriented efficaciously the delivery of paracrine factors in vivo . Finally, we demonstrate that an improved combination as here proposed of hMSCs and biomimetic hydrogel is able to immunomodulate significantly the pro-inflammatory environment in a SCI mouse model, increasing M2 macrophagic population and promoting a pro-regenerative environment in situ.